CHILDREN’S STORYBOOKS IN STRENGTHENING CHILDREN’S CHARACTER - Syahruni Junaid; Faidah Yusuf (International Conference on Social and Islamic Studies, 2021)
The aim of this research is to find out how children's storybook in strengthening children’s character. The rapid development of today's era shows the phenomenon that children generally experience a setback in terms of moral intelligence, although not intellectually. There is a tendency that it is difficult for children to communicate using the correct ethical level, also in terms of speaking and behaving politely, both towards friends in their age and those who are older. This of course has an impact on decreasing their sensitivity to the surrounding which is of course a worrying phenomenon. This research uses descriptive qualitative. One of the factors causing this phenomenon is the decline in the culture of reading of qualified children story books in the daily life of today's society. This is due to the rapid flow of technology that makes children very dependent on technological tools to play games, network in cyberspace and also carry out various other activities, spending time in front of TV and other media. All of this, of course, either directly or indirectly, makes children grow passive in communicating in the real world. They tend to communicate only in one direction, only imitating and adapting without learning the context and concepts of manners so they do not understand how to communicate properly and correctly. Departing from the above background which then prompted this research to be carried out. Researchers see the challenges in this technological era to children's moral deficiencies and one solution is to reactivate the use of picture story books in children. The study began by conducting a survey on the feasibility of picture story books circulating in society today and continued by providing an introduction and habituation to a sample of children with different economic backgrounds and quality of education to find out how the stories they read contributed towards their character in the early stages.